Differentiated Learning with Teaching At The Right Level (Tari) Approach in Al Islam and Kemuhammadiyahan Learning: Pembelajaran Berdiferensiasi Dengan Pendekatan Teaching At The Right Level (Tari) Pada Pembelajaran Al Islam Dan Kemuhammadiyahan - Astutik, Anita Puji; Amrullah, Muhlasin; Shalahuddin, Rahmad (Universitas Muhammadiyah Sidoarjo, 2024)
The COVID-19 pandemic in Indonesia has forced education to transition from face-to-face learning to online learning. This shift has posed various challenges, especially in terms of communication and students' understanding of the material. Educators are expected to have teaching strategies that capture students' attention and ensure a deep understanding of the material being taught. This transformation challenges educators to be more creative and adaptive in managing Distance Learning (PJJ). One effective approach is Teaching at the Right Level (TaRL). The TaRL approach emphasizes diagnostic assessments to evaluate students' potential, characteristics, needs, and developmental stages. Based on the assessment results, educators can plan appropriate learning processes and group students according to their skill levels. This learning process is complemented by formative and summative assessments to evaluate students' understanding and progress. With this systematic approach, it is hoped that the challenges of online learning can be addressed, and learning objectives can be optimally achieved.